A computational model of student cognitive processes while solving a critical thinking problem in science. Issue 2 (4th March 2019) - Lamb, Richard; Firestone, Jonah; Schmitter-Edgecombe, Maureen; Hand, Brian
Abstract: Critical thinking when engaged in science problem solving around even simple tasks such as the Piagetian volume conservation task is a complex endeavor. Tasks such as the conservation task often require the interaction of multiple cognitive systems. Parity judgment, retrieval, and lateral thinking are three examples of such systems interacting with critical thinking during a student's attempt to solve the Piagetian task. The purpose of this computational ablation study is to establish the role of critical thinking as a necessary component of a system of cognition used for the completion of the Piagetian volume conservation task. This ablation study consists of three phases. The confidence interval between the ablation model and the elementary students do not overlap, indicating they are not statistically significantly different. This provides evidence that the model successfully emulates aspects of human cognition and the model can provide a robust picture of science student cognitive processes.